(untitled) (Evidence-Based Pharmacotherapy in Clinical Practice, 2025)
Author Dr Raghu Ram Jampala Professor, Department of Pharmacy Practice, Sultan-ul-Uloom College of Pharmacy, Hyderabad, Telangana, India Abstract Clinical decision-making consists of structured analytical processes for selecting optimal therapeutic interventions. Quantitative risk-benefit assessment utilizes absolute risk reduction, number needed to treat, and harm metrics to evaluate treatment options. Patient values and preferences significantly influence treatment selection through systematic preference elicitation methods. Shared decision-making protocols facilitate collaborative treatment planning between healthcare providers and patients through structured communication frameworks. Clinical judgment development requires integration of theoretical knowledge, practical experience, and pattern recognition skills. Decision analysis models incorporate probability estimates and outcome utilities to optimize therapeutic choices under uncertainty. Keywords: Risk-benefit analysis, Patient preferences, Decision analysis, Clinical judgment, Therapeutic selection VIEW PDF